Prevalence of Fasciola hepatica and gastrointestinal parasites in bovine of the Amazonas Region, Peru - Julon, Deyvis (2020)
The aim of this study was to determine the prevalence of Fasciola hepatica and gastrointestinal parasites in bovines from five districts of the Amazon Region, Peru. A total of 803 bovine faecal samples were collected between October and December 2015 and were analyzed by the coprological spontaneous sedimentation technique. The results indicated a global prevalence of F. hepatica of 59.5%, with a higher prevalence in the districts of Yambrasbamba and Florida, while the prevalence of gastrointestinal parasites was 29.1%, predominating in the districts of Molinopampa and Huambo. The variables origin, category and breed were factors that influenced the degree of infestation by F. hepatica and gastrointestinal parasites (p<0.05), while sex was not significant.